Russian Religious Philosophy about the Spiritual Bases of Economic Activity - Vladimir Borisovich Aleksandrov (Управленческое консультирование)
In article are considered understanding of the nature of economic activity peculiar to the Russian philosophy. The main attention is concentrated on the idea of the spiritual bases of economic process which is put forward by the Russian philosophers, the critic by them absolutizations of the “economic person” understood in the spirit of rationalism, its separation from integrity of life as the subject of culture. Development of idea of the spiritual foundations of economy was carried out by V. S. Solovyov believing that the person is based not on rational calculation, but aspiration to the benefit. In article denial by the philosopher of economic laws and his statement is analyzed that the only law to which the person submits, the moral law is. According to philosophy of economy of S. N. Bulgakov the spiritual nature of economic activity is a consequence of its conditionality integrity of culture which itself has an economic basis, i. e. develops thanks to economic interaction with surrounding reality. In the light of such approach the anthropological perspective is of particular importance. Bulgakov arrives at idea according to which every era has the type of “the economic person” which features aren’t “reflex” of the economic relations, and are caused by all spirit of economy, i. e. integrity of culture. For the Russian philosophy the specific understanding of the Supreme purpose of economic activity is peculiar. As that in it the nature hominifying in space scale is considered. For Solovyov the hominifying is a spiritualizing of the nature, for Bulgakov - the movement in the direction of a life celebration. In article attempt to correlate representations of the Russian philosophers to those processes which happen in modern economy and some ideas on a wire of these processes existing in philosophical and economic thought of our time becomes.